Endoscope-Assisted Transoral Fixation of Mandibular Condyle Fractures: Submandibular Versus Transoral Endoscopic Approach. Issue 5 (July 2016) - Hwang, Na-Hyun; Lee, Yoon-Hwan; You, Hi-Jin; Yoon, Eul-Sik; Kim, Deok-Woo
Abstract : Abstract: In recent years, endoscope-assisted transoral approach for condylar fracture treatment has attracted much attention. However, the surgical approach is technically challenging: the procedure requires specialized instruments and the surgeons experience a steep learning curve. During the transoral endoscopic (TE) approach several instruments are positioned through a narrow oral incision making endoscope maneuvering very difficult. For this reason, the authors changed the entry port of the endoscope from transoral to submandibular area through a small stab incision. The aim of this study is to assess the advantage of using the submandibular endoscopic intraoral approach (SEI). The SEI approach requires intraoral incision for fracture reduction and fixation, and 4 mm size submandibular stab incision for endoscope and traction wires. Fifteen patients with condyle neck and subcondyle fractures were operated under the submandibular approach and 15 patients with the same diagnosis were operated under the standard TE approach. The SEI approach allowed clear visualization of the posterior margin of the ramus and condyle, and the visual axis was parallel to the condyle ramus unit. The TE approach clearly shows the anterior margin of the condyle and the sigmoid notch. The surgical time of the SEI group was 128 minutes and the TE group was 120 minutes ( P >0.05). All patients in the TE endoscope group were fixated with the trocar system, but only 2 lower neck fracture patients in the SEI group required a trocar. The other 13 subcondyle fractures were fixated with an angulated screw driver ( P <0.05). There were no differences in complication and surgical outcomes. The submandibular endoscopic approach has an advantage of having more space with good visualization, and facilitated the use of an angulated screw driver.